Histiocytic Sarcoma Involving Cervical Vertebra: A Case Report and Review of the Literature - Eshagh Bahrami; Masoumeh Najafi; Amin Jahanbakhshi; Jaber Hatam; Saadat Molanaei; Patrizia Ciammella; Salvatore Cozzi (Brain Sciences, 2022)
Histiocytic sarcoma (HS) is a rare neoplasm composed of cells with immunohistochemical characteristics of mature histiocytes. It can be disseminated or localized and usually involves the skin, spleen, and gastrointestinal tract. Primary involvement of the vertebral column is extremely rare. We report a 29-year-old female who presented with neck pain and had a destructive 35*43*48 mm lesion in C2 with a paravertebral extension. The initial biopsy did not lead to the correct diagnosis. She later developed dysphagia, and the anterior approach was used for tumor decompression. The diagnosis of cervical histiocytic sarcoma was made, and she underwent radiotherapy. The follow-up MRI showed a marked response to radiotherapy. Here, we report the first case of cervical HS, review all cases of vertebral HS, compare patients’ characteristics and clinical courses, and discuss diagnostic nuances and treatment options.